Combining Diary and Guided Strategies for Writing Difficulties - Ismiati Ismiati; Iin Lailatul Fitria (Journal of Languages and Language Teaching, 2021)
Complexities of English writing still become big challenges for university students who study English as their majority. Diary and guided writing are two strategies which are commonly separately implemented in writing classes. Among the number of the strengths, there must be the weaknesses when Diary and guided strategies are separately practiced for writing class. Implementing diary writing strategy without continuously guidance may not optimally help students reducing the writing difficulties. This study tried to combine both of the strategies to identify and reduce the students’ writing difficulties. First until eight grade students at English study program were randomly selected as the research subjects. Qualitative approach was applied. The data was obtained by implementing diary writing practice combined with the writing guidance during one month as well as observation, in-depth interview and FGD. Result shows that students got difficulties to apply proper vocabulary, grammar, and mechanic in their writing. Grammar was the most difficult aspects.  Further, combining diary and guided strategies could reduce the students’ writing difficulties.